Brain FADE syndrome: the final common pathway of chronic inflammation in neurological disease - Hanafy, Khalid A.; Jovin, Tudor G. (Frontiers in Immunology, 2024)
Importance: While the understanding of inflammation in the pathogenesis of many neurological diseases is now accepted, this special commentary addresses the need to study chronic inflammation in the propagation of cognitive Fog, Asthenia, and Depression Related to Inflammation which we name Brain FADE syndrome. Patients with Brain FADE syndrome fall in the void between neurology and psychiatry because the depression, fatigue, and fog seen in these patients are not idiopathic, but instead due to organic, inflammation involved in neurological disease initiation.Observations: A review of randomized clinical trials in stroke, multiple sclerosis, Parkinson's disease, COVID, traumatic brain injury, and Alzheimer's disease reveal a paucity of studies with any component of Brain FADE syndrome as a primary endpoint. Furthermore, despite the relatively well-accepted notion that inflammation is a critical driving factor in these disease pathologies, none have connected chronic inflammation to depression, fatigue, or fog despite over half of the patients suffering from them.Brain FADE Syndrome is important and prevalent in the neurological diseases we examined. Classical "psychiatric medications" are insufficient to address Brain FADE Syndrome and a novel approach that utilizes sequential targeting of innate and adaptive immune responses should be studied.